Is Human Vomeronasal Organ A Myth or A Neglected Structure? - Fırat, Ayşegül; Önerci Çelebi, Özlem; Hayran, Hatice Mürvet (Acta Medica, 2022)
The human vomeronasal organ (VNO) is a structure situated under the anteroinferior side of the nasal septum. It is mainly described in the rodents and found as a part of the accessory olfactory system. It has been shown to consist of specialized olfactory sensory cells, which function in perception of pheromones. With a large number of literature on the human VNO, there is little concensus of its persistence and functionality in human. During a routine dissection of nasal cavity, we recognized a one-sided vomeronasal pit in one of the six fresh-frozen cadavers (17 %) and described the position and structure of this rare structure morphologically. The present study summarizes the literature about the VNO and describes its structural and functional findings.